Application of Mnemonic Method to Improve English Language Learning Outcomes - Haryadi, Rofiq Noorman; Sunarsi, Denok (Sapta Arga Nusantara, 2024)
In the era of globalization, mastery of the English language has become a fundamental prerequisite in the academic world, especially for students. This study aims to explore the effectiveness of mnemonic methods in improving English language learning at SMK Bina Mandiri Multimedia. The mnemonic method, which relies on forming associations between new information and what is already known, was applied to facilitate students' memory of vocabulary and language structures. The study employed an experimental design with a pretest-posttest control group approach, involving 66 students divided into experimental and control groups. The results showed significant improvements in engagement and academic performance in the experimental group. There was a notable increase in the number of students actively asking and answering questions, as well as applying mnemonic techniques. The average score increased from 34 in Cycle 1 to 72 in Cycle 2, indicating substantial improvement in learning outcomes. The study concludes that the application of mnemonic methods is effective in enhancing English language learning, by improving memory retention and learning motivation.